(3GdJYQja HhLhH Mb GdhGdOjfs - (3eMeO Hf Ydj Hf YKeGf Hf Ydj GdcQGLcj, CHh GdaJMs
(3ChdgG (B:s
(3EYde CjgG GdhdO GdMHjH GdHGQ GdfLjH bje GdfaS s
(3BNQgG (B:s
(3Gf CLYd dc JPcQI hdef ShGc JHUQI CYGPc Gddg ef GdRddI hGdMeO ddg ceG gh CgdI heSJMbg hUdhGJg Ydi NjQ Ndbg eMeO hBdg GdWGgQjf hMSHfG Gddg hfYe Gdhcjd s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(12/433) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs